Implementasi Program GEMPITA sebagai Transformasi Pendidikan Islam di Sekolah Umum - Falya Hamidah; Asyifa Cincin Pambajeng; Muhamad Miftahul Ahyar; Kuni Fathiyatul Mubarokah; Oktio Frenki Biantoro (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2026)
This study explores the implementation of the GEMPITA (Gerakan Mengkaji Kitab Suci Kita) program as a form of Islamic education transformation in public schools, focusing on SMP Negeri 6 Salatiga. The research employed a qualitative case study method through interviews, observations, and documentation. The findings reveal that GEMPITA functions as a structured and sustainable religious literacy initiative that enhances students’ Qur’anic reading ability, fosters religious motivation, and instills moral and disciplined character through daily spiritual routines. The program includes Qur’an reading, Duha prayer, congregational Zuhur and Asar prayers, and Friday religious activities. The results indicate that GEMPITA successfully strengthens Islamic values and character formation among students while promoting interfaith tolerance and inclusivity. Despite some challenges such as time constraints and varied student motivation, GEMPITA has become a model for integrating Islamic education values into general education. The study concludes that this program is an effective medium for realizing holistic education that harmonizes spiritual and intellectual development in a multicultural environment.